Strengthening coordination and collaboration of one health approach for zoonotic diseases in Africa - Yewande Alimi; James Wabacha (BMC, 2023)
Abstract Despite the One Health progress made in some African countries in addressing zoonotic disease outbreaks, many still lack formal and funded One Health programs. Countries lack diagnostic capacity for zoonotic diseases, coordinated surveillance mechanisms, multisectoral response strategies and skilled workforce. With the devasting impacts of zoonotic disease outbreaks, recent epidemics have caused a loss of lives and negatively impacted the economy. Strengthening One Health approach across African Union (AU) Member States will improve the continent's ability and capacity to efficiently prevent, detect, and respond to emerging and re-emerging zoonotic diseases. The policy and practice changes needed to address zoonotic diseases require strong political commitment, financial investments, and institutionalised national One Health programs. The African Union endorses a One Health approach in which multiple sectors work jointly to raise awareness, gather credible data, implement programs, and promote evidence-based policy and practice in improve human, animal, and environmental health. The African Union working through its technical agencies set up an interagency multidisciplinary group "the One Health Coordinating Group on Zoonotic Diseases" to strengthen coordinated surveillance, prevention and control of zoonotic diseases on the continent. There is an urgent need to strengthen the coordination of One Health activities across the African continent. The African Union will leverage its unique political position on the continent to raise awareness, secure commitments, and influence policy at the head of state level. This manuscript highlights the opportunity to improve and strengthen One Health coordination and harmonisation of efforts through a continental strategy for zoonotic disease control.